Effect of the doped fibre length on soliton pulses of a bidirectional mode-locked fibre laser - Ahmad, H.; Kutty, N.A. Alwi; Zulkifli, Mohd Zamani; Harun, S.W. (IOP Publishing, 2015)
A passively bidirectional mode-locked fibre laser is demonstrated using a highly concentrated erbium-doped fibre (EDF) as a gain medium. To accomplish mode-locked operation in a short cavity, use is made of carbon nanotubes (CNTs) as a saturable absorber. Soliton pulses are obtained at a wavelength of 1560 nm with a repetition rate ranging from 43.92 MHz to 46.97 MHz and pulse width stretching from 0.56 ps to 0.41 ps as the EDF length is reduced from 60 cm to 30 cm.